Heat Shock Protein 70 and Heat Tolerance in Early-Age Feed Restricted Broiler Chickens - Mat Taib, Che Norma (2000)
The objectives of this study are to evaluate the effect of various degree of neonatal feed restrictions on heat tolerance later in life, the importance of heat shock protein 70 (HSP 70) in eliciting thermotolerance in broilers and the relationship between heat stress and occurrence of programmed cell death (apoptosis). Broiler chicks that were subjected to 80% feed restriction (F80). 60% feed restriction (F60) and 40% feed restriction (F40) or ad libitum feeding from 4 to 6 days of age were exposed to high ambient temperatures (38±1·C) for 2hr/day from 35 to 42 days of age. Short term feed restriction during the first week of life caused retardation of growth. Although feed restriction reduced initial growth, birds grew more rapidly than those fed ad libitum (AL) during refeeding. One day following the imposition of feed limitation, higher levels of HSP 70 expression in the brain tissues and increased helerophil/lympocyte (H/L) ratios were noted among F60 and F40 birds. Birds subjected to fasting early in life (F60) improved HSP 70 expression, growth, survivability, and reduced H/L ratios compared to those fed AL and FBO in response to the heat treatment. The survivabile rate and H/L ratios of F40 chicks were similar to those attained by other feeding regimens (AL and FBO). Irrespective of feeding regimen, heat stress resulted in an increase in serum glucose level and appearance of programmed cell death (apoplosis) in the thymus glands. These resuHs suggest that neonatal fasling evokes heat tolerance laler in life through enhanced expression of HSP 70. Exposing birds to feed reslriction of either lower (FBO) or higher (F40) severity do not to have profound influence on subsequent resistance to heat stress later in life.